PEMBINAAN KETERAMPILAN UNTUK MENINGKATKAN SKILL NARAPIDANA PEMASYARAKATAN KELAS 1 MALANG DI MASA PANDEMI COVID-19 - Nafiah, Annisau; Sutadji, Eddy; Nurmalasari, Riana (Jurnal Graha Pengabdian, 2020)
Abstrak: Dalam rangka meningkatkan keterampilan warga binaan pemasyarakatan Lapas Kelas 1 Malang, rutin diadakan pelatihan guna membekali para warga binaan agar setelah keluar nanti bisa mandiri secara ekonomi dan mempunyai soft skill. Melalui hal ini diharapkan mereka tidak akan kebingungan lantaran setelah keluar Lapas sudah memiliki keahlian. Meskipun sedang dalam masa pandemi, program pengembangan pembinaanÂ  kemandirian tetap bejalan meskipun tidak sebanyak kegiatan saat sebelum mewabahnya virus covid-19. Kegiatan pengabdian masyarakat ini bertujuan untuk memberikan ilmu dan keterampilan bagi warga binaan Kelas 1 Kota Malang, sehingga ketika mereka menghirup udara bebas nanti mereka punya bekal ketampilan yang dapat dikembangkan di rumah sebagai bentuk usaha dalam menciptakan lapangan pekerjaan sendiri yang halal. Harapannya nanti, mereka dapat berapdaptasitasi dan diterima masyarakat menjadi pribadi yang baik. Metode pelaksanaan pengabdian masyarakat ini dimulai dari survey mitra, menganalisis masalah, memecahkan masalah, dan evaluasi. Berdasarkan hasil pelatihan yang sudah dilaksanakan, kegiatan berjalan dengan lancar meskipun menemui sedikit kendala teknis pada sarana dan prasaranan yang tersedia di Lapas kelas 1 Malang. Antusias warga binaan memberikan respon yang sangat positif sehingga kegiatan yang serupa dapat terus dilaksanakan guna meningkatkan skill dan ilmu baru bagi warga binaan.Abstract: In order to improve the skills of the Class 1 Correctional Facilities in Malang, routine training is held to equip the assisted residents so that after leaving they can be economically independent and have soft skills. Through this, it is hoped that they will not be confused because after leaving prison they already have expertise. Even though it is currently in a pandemic period, the self-reliance development program is still running, although not as many activities as before the Covid-19 virus outbreak. This community service activity aims to provide knowledge and skills for the Class 1 members of Malang City, so that when they breathe the free air, they will have skills that can be developed at home as a form of effort to create their own halal jobs. Hopefully later, they can adapt and be accepted by society to be good people. This method of implementing community service starts from partner surveys, problem analysis, problem solving, and evaluation. Based on the results of the training that had been carried out, the activity ran smoothly even though it encountered a few technical problems with the facilities and infrastructure available at the Class 1 Prison in Malang. The enthusiasm of the assisted residents gave a very positive response so that similar activities could continue to be carried out in order to improve new skills and knowledge for the assisted residents. the activity ran smoothly even though it encountered a few technical problems with the facilities and infrastructure available at the Class 1 prison in Malang. The enthusiasm of the assisted residents gave a very positive response so that similar activities could continue to be carried out in order to improve new skills and knowledge for the assisted residents. the activity ran smoothly even though it encountered a few technical problems with the facilities and infrastructure available at the Class 1 prison in Malang. The enthusiasm of the assisted residents gave a very positive response so that similar activities could continue to be carried out in order to improve new skills and knowledge for the assisted residents.